Functional Evaluation of Open Carpal Tunnel Release in Carpal Tunnel Syndrome Patients - Swagat Mahapatra; Devta Singh; Prakhar Mishra; Jaydeep Patel; Madhusudan Mishra; Animesh Gupta (Journal of Orthopedics, Traumatology and Rehabilitation)
Introduction: Carpal tunnel syndrome is the most common peripheral neuropathy and develops due to compression of the median nerve in the carpal tunnel. It is a significant health problem because it affects the daily activities and the quality of life. Carpal tunnel syndrome is a musculoskeletal disorder related to work activity in affected individuals that is caused by strain and repetitive activity, making it a very common problem across manual laborers. Surgeons and clinicians from different departments frequently meet cases of it. The decompression of the median nerve is the main target of the treatment, and carpal tunnel syndrome can usually be treated effectively through surgical methods. Objective: The objective of this study was to evaluate the functional outcome of open carpal tunnel release in carpal tunnel syndrome and analyze the risk factors and epidemiological patterns associated with carpal tunnel syndrome. Materials and Methods: This prospective cohort study was performed in the department of orthopedics at our institute for 8 months (January 2021 to August 2022) on carpal tunnel syndrome patients of either sex age ranging 20–60 years who attended orthopedic outpatient department and orthopedic wards, and who confirmed consent and found fitted according to inclusion criteria were recruited for this study. A predesigned patient’s pro forma for data collection was used. The Carpal Tunnel Syndrome 6-point Questionnaire, including the Quick Disabilities of the Arm, Shoulder, and Hand Questionnaire, was used. Results: The mean age was 44.9 ± 10.2 years with the majority of the cases between 41 and 6 years (67.3%). The majority of the studied cases were female (77.6%), followed by males (22.4%). In the majority of cases, the right hand was the dominant hand (58.7%), and also, the right hand was the most operated hand (55.1%). The degree of carpal tunnel syndrome was compared before surgery, after 3 months of surgery, and after 6 months of surgery, and the association was found statistically significant (P < 0.001) as the results improved significantly over time. The electrophysiological data of open carpal tunnel release syndrome was compared, and all the motor and sensory parameters improved over time significantly (P < 0.05). After 3 months of surgery and after 6 months of surgery, it was found that the Disabilities of the Arm, Shoulder, and Hand Score reduced significantly after 6 months of the surgery (P < 0.001). Conclusion: In conclusion, the Six-Item Carpal Tunnel Syndrome Symptoms Scale Questionnaire can be used along with other questionnaires to usefully determine the clinical improvements after surgical treatment of patients with carpal tunnel syndrome. Furthermore, we consider the evaluated parameters, our results suggest that open carpal tunnel release was a reliable and safe procedure in the treatment of idiopathic carpal tunnel syndrome. Our results revealed that there was a significant improvement in the clinical outcomes after the carpal tunnel syndrome surgery.